1993
DOI: 10.1021/np50097a002
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulant Agents from Andrographis paniculata

Abstract: EtOH extract and purified diterpene andrographolides of Andrographis paniculata (Acanthaceae) induced significant stimulation of antibody and delayed type hypersensitivity (DTH) response to sheep red blood cells (SRBC) in mice. The plant preparations also stimulated nonspecific immune response of the animals measured in terms of macrophage migration index (MMI) phagocytosis of 14C-leucine labelled Escherichia coli and proliferation of splenic lymphocytes. The stimulation of both antigen specific and nonspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
203
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(205 citation statements)
references
References 8 publications
0
203
0
2
Order By: Relevance
“…It has been traditionally used as a remedy against diabetes (Norhaida, 1994), hypertension (Ahmad and Asmawi, 1993), inflammation (Patarapanich et al, 2007) and cobra bite (Selvanayagam et al, 1994). Extensive 46 research revealed that A. paniculata has a surprisingly broad range of pharmacological effects and some of them are extremely beneficial and include anticancer (Kumar et al, 2004), anti HIV (Chang andYeung, 1988), anti AIDS (Stephen and Comac, 2000), hepatoprotective (Handa and Sharma, 1990) and immunostimulatory (Puri et al, 1993). Other pharmacological effects include; antimalarial (Misra et al, 1992), antityphoid (Sabu, 2006), antiviral (Wiart et al, 2005), antifungal (Sabu, 2006), antibacterial (Mishra et al, 2009), antidiarrhoeal (Gupta et al, 1993), antipyretic (Vedavathy andRao, 1991), antiinflammatory (Chang andBut, 1986), antidiabetic (Zhang and Tan, 2000), antithrombotic (Yeung et al, 1987), cardiovascular Zhang, 2004), antivenom (Chang andBut, 1986), antifertility (Sakila et al, 2009) and psychopharmacological activity (Mandal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been traditionally used as a remedy against diabetes (Norhaida, 1994), hypertension (Ahmad and Asmawi, 1993), inflammation (Patarapanich et al, 2007) and cobra bite (Selvanayagam et al, 1994). Extensive 46 research revealed that A. paniculata has a surprisingly broad range of pharmacological effects and some of them are extremely beneficial and include anticancer (Kumar et al, 2004), anti HIV (Chang andYeung, 1988), anti AIDS (Stephen and Comac, 2000), hepatoprotective (Handa and Sharma, 1990) and immunostimulatory (Puri et al, 1993). Other pharmacological effects include; antimalarial (Misra et al, 1992), antityphoid (Sabu, 2006), antiviral (Wiart et al, 2005), antifungal (Sabu, 2006), antibacterial (Mishra et al, 2009), antidiarrhoeal (Gupta et al, 1993), antipyretic (Vedavathy andRao, 1991), antiinflammatory (Chang andBut, 1986), antidiabetic (Zhang and Tan, 2000), antithrombotic (Yeung et al, 1987), cardiovascular Zhang, 2004), antivenom (Chang andBut, 1986), antifertility (Sakila et al, 2009) and psychopharmacological activity (Mandal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Haemagglutination antibody (HA) titre Puri et al (1993) described the method for haemagglutination antibody titre. The animals were immunized by injecting 0.1 ml of SRBC suspension containing 0.5 × 10 9 cells intra-peritoneally on day 0.…”
Section: Neutrophil Adhesion Testmentioning
confidence: 99%
“…The study was conducted according to Puri et al (1993) method. Four groups of rats were used as per the treatment groups above.…”
Section: Determination Of Humoral Immune Response -Hemagglutination Amentioning
confidence: 99%